Selective Ionic Transport: Highly Selective Ionic Transport through Subnanometer Pores in Polymer Films (Adv. Funct. Mater. 32/2016). (August 2016) - Wen, Qi; Yan, Dongxiao; Liu, Feng; Wang, Mao; Ling, Yun; Wang, Pengfei; Kluth, Patrick; Schauries, Daniel; Trautmann, Christina; Apel, Pavel; Guo, Wei; Xiao, Guoqing; et al.
Abstract : Polymer nanopores have great potential for ultrafiltration, desalination, and energy conversion because of their robustness, flexibility, and efficiency in large‐scale production. Yet a challenge in controlling the size to subnanometer limits their performance. F. Liu, Y. Wang, and co‐workers describe on page 5796, the generation of negatively charged subnanometer polymer pores that exhibit ultra‐high ionic transport selectivity and a unique order as Li + >Na + >K + >Cs + ≫Mg 2+ >Ca 2+ >Ba 2+ ≫blocked heavy metal ions and anions.